2009
DOI: 10.1111/j.1654-109x.2009.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Herb layer changes (1954‐2000) related to the conversion of coppice‐with‐standards forest and soil acidification

Abstract: Question: Did the composition of the herb layer of a deciduous forest on loamy soils sensitive to soil acidification change between 1954 and 2000? How are these change related to the abandonment of traditional coppice-with-standards forest management and increased soil acidification? Location: Central Belgium (Europe). Methods: Twenty semi-permanent phytosociological quadrats from an ancient deciduous forest (Meerdaal forest) were carefully selected out of a total of 70 plots dating from 1954 and were revisite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
98
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 34 publications
11
98
1
6
Order By: Relevance
“…The strong directionality of forest herb layer vegetation shifts is consistent with other resurvey studies ( Fig. 3a; e.g., Lameire et al 2000;Taverna et al 2005;Baeten et al 2009) and appeared to be mainly driven by species losses resulting in nested patterns rather than real species turnover within a plot. The considerable βnes dissimilarities between plot-pairs showed that the 2009 community was generally nothing more than an impoverished subset of the 1979 vegetation (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The strong directionality of forest herb layer vegetation shifts is consistent with other resurvey studies ( Fig. 3a; e.g., Lameire et al 2000;Taverna et al 2005;Baeten et al 2009) and appeared to be mainly driven by species losses resulting in nested patterns rather than real species turnover within a plot. The considerable βnes dissimilarities between plot-pairs showed that the 2009 community was generally nothing more than an impoverished subset of the 1979 vegetation (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have for instance found clear evidence for the importance of changes in forest management or canopy succession (e.g., Kirby and Thomas 2000;Van Calster et al 2008;Rogers et al 2008;Baeten et al 2009;Keith et al 2009), changed deer abundances (e.g., Kirby and Thomas 2000;Rooney et al 2004;Taverna et al 2005), increased atmospheric deposition of acidifying and eutrophying pollutants (e.g., Lameire et al 2000;Van Calster et al 2007;Baeten et al 2009;Keith et al 2009) or past habitat loss and fragmentation (e.g., Rogers et al 2009). For Lady Park Wood, canopy succession and deer (over)abundance are probably the main drivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this investigation show a similar pattern of species ordination, where the themophilous oak forest species were placed between mesic and acidophilous species. However, the niche is probably only temporary, since succession processes have been observed after cessation of coppicing [6,7,9]. This could lead to a succession from species-rich to a typical mesic forest [5].…”
Section: Discussionmentioning
confidence: 99%
“…Short-rotation coppices are often established for afforestation of unused agricultural soils and restoration of landfills (Nixon et al 2001). The most frequently claimed advantage of coppice is an increase in the overall biodiversity of the site, especially in terms of heliophile forest species (Spitzer et al 2008, Van Calster et al 2007, Baeten et al 2009). Due to its low managing costs, coppice seems a valuable alternative for small-and medium-sized-forest owners, as well as for the regeneration of stands where seedling establishment is difficult.…”
Section: Introductionmentioning
confidence: 99%